1984
DOI: 10.1093/jn/114.4.671
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of L-Carnitine-Supplemented Total Parenteral Nutrition on Tissue Amino Acid Concentrations in Piglets

Abstract: Miniature piglets underwent total parenteral nutrition (TPN) with and without L-carnitine supplementation during a 7-day period. Thereafter the tissue amino acid concentrations of liver, heart, skeletal muscle and brain were determined and compared to those of orally fed animals. The altered tissue amino acid concentrations during TPN without carnitine returned to normal when L-carnitine was supplemented. The most striking changes of tissue concentrations showed taurine in liver, muscle and brain and ethanolam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…phosphoserine. y-aminobutyrate and taurine in brain [80], Moreover, according to some ob servations, carnitine availability may alter the nitrogen balance of the organism [81. 82] providing further evidence for a relationship between certain elements of nitrogen metab olism and carnitine.…”
Section: Carnitine and Metabolism O F Nitrogen Compoundsmentioning
confidence: 99%
“…phosphoserine. y-aminobutyrate and taurine in brain [80], Moreover, according to some ob servations, carnitine availability may alter the nitrogen balance of the organism [81. 82] providing further evidence for a relationship between certain elements of nitrogen metab olism and carnitine.…”
Section: Carnitine and Metabolism O F Nitrogen Compoundsmentioning
confidence: 99%
“…Furthermore, L ‐carnitine appears to play a role in the metabolism of amino acids. Animal tissues often contain acyl‐carnitine derivatives of branched‐chain amino acids (BCAA: leucine, isoleucine or valine) (Bohles et al. 1984; Ji et al.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, L-carnitine appears to play a role in the metabolism of amino acids. Animal tissues often contain acylcarnitine derivatives of branched-chain amino acids (BCAA: leucine, isoleucine or valine) (Bohles et al 1984;Ji et al 1987;Weisdorf et al 1991). Hayashi et al (1996) observed a glutamine-sparing effect of L-carnitine in tissues of rats.…”
Section: Introductionmentioning
confidence: 99%
“…The L-carnitine concentration gradient was even more pronounced between muscle and liver tissues (Ozório et al 2001). The ability to take up and retain dietary carnitine was observed in other species, such as Atlantic salmon Salmo salar L. (Ji et al 1996), red seabream Pagrus major (Chatzifotis and Takeuchi 1997), rabbits (Bell et al 1992), piglets (Böhles et al 1984), rats (Tsai et al 1974), among other species (Li et al 2017).…”
Section: Discussionmentioning
confidence: 92%